Polyamide composite material as well as preparation method and application thereof
By adding nylon chain extender and phosphate additives to the polyamide composite material, combining polyamide resin with specific melting point and thermal weight loss properties, the problem of insufficient strength and reflectivity in the LED bracket is solved, and the problem of polyamide composite material is achieved. Higher performance.
Patent Information
- Application Number
- CN202411090363.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-08-09
AI Technical Summary
Existing polyamide composites have poor strength and reflectivity in LED stents, making it difficult to meet application needs, especially when recycled materials after being added to industrial.
Using the combination of polyamide composition A and industrial post-recycling materials, the addition ratio and thermal stability of polyamide composition B are adjusted to improve the material by adding nylon chain extenders and phosphate additives to the polyamide resin. reflectivity and intensity.
It effectively improves the reflectivity and strength of polyamide composite materials, making them perform better in LED brackets and meet application needs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer compound compositions, and more specifically, to a polyamide composite material and a preparation method and application thereof. Background Art
[0002] Many countries and regions have proposed their own emission reduction targets. The plastic products industry is currently exploring three types of renewable materials: post-consumer materials (PCR-Post Consumer Resin), post-industrial materials (PIR-Post Industrial Resin) and bio-based materials (Bio-based material); among them, PCR is the material of post-consumer recycled products that have been pre-processed (disassembly, sorting, cleaning), crushed, melted, and re-granulated; PIR is the direct recycling and re-granulation of materials such as sprues, sub-brands, and defective products generated when the factory injects products. In particular, the ultra-high mold cavity injection molding process in the LED industry will produce a large amount of post-industrial recycled materials; in the existing technology, post-industrial recycled materials are generally mixed and used in combination with new materials. However, in the actual application process, it is found that the addition of post-industrial recycled materials to polyamide composite materials used for LEDs will result in poor strength and reflectivity of LED brackets, making it difficult to meet application requirements. Summary of the invention
[0003] The purpose of the present invention is to overcome the defects and shortcomings of the existing polyamide composite materials containing post-industrial recycled materials, such as poor strength and reflectivity, and to provide a polyamide composite material.
[0004] Another object of the present invention is to provide a method for preparing the polyamide composite material.
[0005] Another object of the present invention is to provide an application of a polyamide composite material in an LED reflective bracket.
[0006] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0007] The present invention protects a polyamide composite material, comprising a polyamide composition A and a polyamide composition B, wherein the polyamide composition A comprises the following components in parts by weight:
[0008] 35-85 parts of polyamide resin, 7-32 parts of filler, 7-32 parts of white pigment, 0.2-2 parts of modification aid, 0.2-2 parts of phosphate and its derivatives; the modification aid is a nylon chain extender; the melting point of the polyamide resin is 270-330°C, and the thermal weight loss at 370°C is less than 15%;
[0009] The polyamide composition B is a polyamide composition A recycled after industrial use;
[0010] The mass proportion of the polyamide composition B in the polyamide composite material is ≤85%.
[0011] The present invention provides a polyamide composite material, which contains post-industrial recycled materials and a polyamide composition A, and adjusts the addition ratio of the polyamide composition B, adjusts the thermal stability of the polyamide resin, and combines a nylon chain extender as a modification aid to allow broken molecular chains to be repolymerized. However, the nylon chain extender and the rearrangement of the molecular chains are competing reactions. We surprisingly found that the use of phosphate additives can effectively inhibit the rearrangement of the molecular chains without affecting the reaction between the molecular chains, so the strength and reflectivity of the polyamide composite material can be effectively improved.
[0012] It should be noted that those skilled in the art should understand that the polyamide composition A recycled after industrial use is the nozzle material produced by injection molding of the polyamide composition A described in the present invention.
[0013] Specifically, the polyamide resin is a semi-aromatic polyamide resin.
[0014] The semi-aromatic polyamide resin is composed of units formed by aliphatic diamines with 3 to 36 carbon atoms and aromatic diacids; preferably aliphatic diamines with 6 to 10 carbon atoms, more preferably aliphatic diamines with 9 or 10 carbon atoms; the aromatic dibasic acid is preferably one or more of terephthalic acid and isophthalic acid.
[0015] Specifically, the semi-aromatic polyamide includes at least one of PA6T, PA4T, PA6I, PA9T, PA10T and PA12T.
[0016] In some specific embodiments, the polyamide composition B is obtained by injection molding the polyamide composition A described in the present invention, the injection molding temperature is 350°C-340°C-330°C-330°C-320°C, and the injection molding speed is 320-380 mm / s.
[0017] In some specific embodiments, the polyamide composition B has an L value greater than 70, an a value of -5 to 5, and a b value of -15 to 15.
[0018] The polyamide resin has an L value of >80, an a value of -5 to 0, and a b value of -5 to 5.
[0019] Specifically, the Lab value of the polyamide resin is measured using a Color Eye 7000A colorimeter. The polyamide resin is injection molded, and the sample size is 60 mm×60 mm×0.8 mm.
[0020] The melting point of the polyamide resin in the present invention is 270-330°C. For example, but not limited to, the melting point is 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C or 330°C, etc., which can realize the present invention.
[0021] The polyamide resin of the present invention has a thermal weight loss of less than 15% at 370°C, for example but not limited to less than 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6% or 5%, etc., which can achieve the present invention.
[0022] The mass proportion of the polyamide composition B in the polyamide resin composite material of the present invention is ≤85%, for example but not limited to ≤85%, 80%, 75%, 70%, 65%, 60%, 55% or 50%, etc. can realize the present invention.
[0023] The mass proportion of the polyamide resin in the polyamide composition A is preferably not less than 30%.
[0024] Preferably, the phosphate is a phosphate and its derivatives are one or more of potassium phosphate, sodium phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, phosphate ester, phosphite, and disodium dihydrogen pyrophosphate.
[0025] In a specific embodiment, the phosphite includes one or more of (2,4-di-tert-butylphenyl) pentaerythritol diphosphite, 1,3-phenylene (2,6-methylphenyl) tetraphosphate or hydroquinone bis(diphenyl phosphate).
[0026] Preferably, the mass proportion of the polyamide composition B in the polyamide composite material is 60% to 80%.
[0027] Preferably, the polyamide composition A comprises the following components by weight: 50-70 parts of polyamide resin, 14-25 parts of filler, 14-25 parts of white pigment, 0.6-1.6 parts of modification aid, and 0.5-1 parts of phosphates and their derivatives.
[0028] Specifically, the melting point of the polyamide resin can be tested with reference to ASTM D3418-2003 standard, specifically using a Perkin Elmer Diamond DSC analyzer, in a nitrogen atmosphere, with a flow rate of 40 mL / min, during the test, the temperature is first increased to 340° C. at 10° C. / min, maintained at 340° C. for 2 minutes, then cooled to 50° C. at 10° C. / min, and then increased to 340° C. at 10° C. / min.
[0029] Specifically, the method for determining the thermogravimetric performance of the polyamide resin refers to the standard GB / T 27761-2011.
[0030] Specifically, a Netzsch TG209 analyzer was used in a nitrogen atmosphere with a flow rate of 40 mL / min. During the test, the temperature was first raised to 120°C at 20°C / min, maintained at 120°C for 30 min, then raised to 370°C at 20°C / min, and then retained at 370°C for 60 min. The weight loss from the initial reaching of 370°C to the end of the constant temperature for 60 min was calculated to obtain the 370°C constant temperature retention weight loss.
[0031] Further preferably, the SMT retention rate of the polyamide resin is not less than 80%.
[0032] Specifically, the SMT retention rate determination method is to measure the bending strength of the polyamide resin with reference to the standard ISO 178-2019, and record it as the initial bending strength; then, after the sample has been subjected to SMT, the bending strength is measured again according to the same method, and recorded as the bending strength after SMT; SMT retention rate = bending strength after SMT / initial bending strength*100%.
[0033] Optionally, the relative viscosity of the polyamide resin is 1.8 to 2.4.
[0034] Specifically, the relative viscosity of the polyamide resin can be tested with reference to GB 12006.1-1989 standard.
[0035] Specifically, the relative viscosity of the polyamide at a concentration of 0.25 g / dl was measured in 98% concentrated sulfuric acid at 25±0.01°C.
[0036] Furthermore, the relative viscosity of the polyamide resin is 2.0 to 2.4.
[0037] Specifically, the white pigment is at least one of titanium dioxide, zinc oxide, zinc sulfide, white lead, zinc sulfate, barium sulfate, calcium carbonate, aluminum oxide, silicon dioxide, aluminum oxide, barium carbonate, aluminum nitride, boron nitride, potassium titanate, calcium silicate, aluminum borate, calcium sulfate, and barium sulfate; preferably titanium dioxide.
[0038] Specifically, the filler is at least one of glass fiber, wollastonite, potassium titanate whisker, kaolin or mica.
[0039] The nylon chain extender in the present invention can be selected with reference to the prior art, for example, but not limited to, the nylon chain extender is one or more of anhydride chain extenders, epoxy chain extenders, oxazoline chain extenders, carbonate chain extenders, isocyanate chain extenders, polyamine chain extenders and polyol chain extenders.
[0040] Specifically, the oxazoline chain extender is tert-butyl 4-acetyl-2,2-dimethyloxazoline-3-carboxylate.
[0041] Specifically, the anhydride chain extender is a maleic anhydride grafted ethylene copolymer.
[0042] Specifically, the isocyanate chain extender is meta-xylylene diisocyanate.
[0043] Specifically, the diamine chain extender is one or more of diethylenetriamine, diaminodiaminemethane, hexamethylenediamine, ethylenediamine, butanediamine or isofluorodionediamine.
[0044] Specifically, the polyol chain extender is one or more of 1,4-butanediol, trimethylolpropane or 1,2-propylene glycol.
[0045] Specifically, it may be BRUGGOLEN M1251 / M1253, BASF chain extender ADR 4368C or CHEMCORD CM 3020 nylon-specific chain extender.
[0046] In addition, the polyamide composition A may further include one or more of an antioxidant, a light stabilizer, an impact modifier, a flame retardant, a fluorescent brightener, a lubricant, a plasticizer, a thickener, an antistatic agent, a release agent or a colorant.
[0047] The present invention also protects a method for preparing the above-mentioned polyamide composite material, comprising the following steps: mixing and melt-extruding the components to obtain the polyamide composite material; specifically, a twin-screw extruder can be used for melt extrusion, and the melt extrusion temperature is 230°C to 330°C.
[0048] An application of the above polyamide composite material in an LED reflective bracket is also within the protection scope of the present invention.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The present invention provides a polyamide composite material, comprising no more than 85% of post-industrial recycled materials and a polyamide composition A. A nylon chain extender is added to the polyamide composition A as a modifying auxiliary agent to cooperate with a phosphate auxiliary agent, and a polyamide resin with a specific melting point and a thermal weight loss performance range is combined to effectively improve the reflectivity and strength of the polyamide composite material. DETAILED DESCRIPTION
[0051] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0052] 1. Raw materials and reagents
[0053] Polyamide resin 1: Vicnyl 700NC003, melting point 316°C, thermal weight loss at 370°C 6.3%, relative viscosity 2.15, manufacturer: Zhuhai Wantong Special Engineering Plastics Co., Ltd.
[0054] Polyamide resin 2: Vicnyl 6100NC003, melting point 290°C, thermal weight loss at 370°C 8.2%, relative viscosity 2.12, manufacturer: Zhuhai Wantong Special Engineering Plastics Co., Ltd.;
[0055] Polyamide resin 3: Vicnyl 702NC003, melting point 316°C, thermal weight loss at 370°C 7.6%, relative viscosity 1.85, manufacturer: Zhuhai Wantong Special Engineering Plastics Co., Ltd.
[0056] Polyamide resin 4: Vicnyl 3100NC003, melting point 343°C, thermal weight loss at 370°C 9.7%, relative viscosity 2.09, manufacturer: Zhuhai Wantong Special Engineering Plastics Co., Ltd.;
[0057] Polyamide resin 5: Vicnyl 400NC003, melting point 305°C, thermal weight loss at 370°C 26%, relative viscosity 2.18, manufacturer: Zhuhai Wantong Special Engineering Plastics Co., Ltd.
[0058] Phosphates and their derivatives 1: (2,4-di-tert-butylphenyl) pentaerythritol diphosphite, purchased from Chemtura Corporation;
[0059] Phosphates and their derivatives 2: disodium dihydrogen pyrophosphate, purchased from Anhui Zhongxu Biotechnology Co., Ltd.;
[0060] The filler is glass fiber, brand E7CS10-03-568H, and the manufacturer is China Jushi Co., Ltd.
[0061] The white pigment is titanium dioxide, brand BLR-895, manufactured by Longbai Group Co., Ltd.
[0062] Modification agent 1: carbonate chain extender, BRUGGOLEN M1251, Bruggemann;
[0063] Modification aid 2: polyamine chain extender, diethylenetriamine, commercially available;
[0064] 2. The polyamide composite materials of the embodiments and comparative examples of the present invention are prepared by the following preparation method:
[0065] Weigh each component according to the formula and mix them evenly, then add them into a twin-screw extruder for melt blending and extrusion granulation to obtain a polyamide composite material;
[0066] Among them, the melt extrusion conditions of the twin-screw extruder are: the temperature of zone 1 is 165°C, the temperature of zone 2 is 230°C, the temperature of zone 3 is 310°C, the temperature of zone 4 is 320°C, the temperature of zone 5 is 320°C, the temperature of zone 6 is 320°C, the temperature of zone 7 is 310°C, the temperature of zone 8 is 310°C, the temperature of zone 9 is 310°C, the temperature of zone 10 is 310°C, and the main engine speed is 450r / min.
[0067] 3. Performance testing
[0068] After the injection molding samples (2.8mm*3.5mm*0.15mm) were subjected to infrared reflow three times, they were randomly divided into two groups, A and B. Group A was tested for light reflectivity after reflow, and Group B was tested for inference power. The infrared reflow used an SMT infrared reflow device with the following setting conditions:
[0069] a. Preheating stage: raise the temperature from room temperature to 150°C within 120 seconds;
[0070] b. Heating stage: raise the temperature from 150°C to 190°C within 90 seconds;
[0071] c. Reflow stage: Raise the temperature to 217°C at a heating rate of 2.5°C per second, then raise the temperature from 217°C to 260°C and then lower it to 217°C within 80 seconds;
[0072] d. Cooling stage: lower the temperature to room temperature at a cooling rate of more than 2°C per second.
[0073] (1) Light reflectivity test after reflow soldering: After the injection molded sample was subjected to infrared reflow soldering three times, the light reflectivity of the sample at 460nm was tested using a Color Eye 7000A colorimeter.
[0074] (2) Tension force test: Place the sample after reflow soldering under a thrust testing machine to test the tensile force of the LED bracket.
[0075] Examples 1 to 11 and Comparative Examples 1 to 6
[0076] The weight percentages of the components of the polyamide composite materials in Examples 1 to 11 and Comparative Examples 1 to 6 and the performance test results are shown in Tables 1 and 2.
[0077] Table 1 Weight percentage of each component of the polyamide composite material in Examples 1 to 11
[0078]
[0079] It should be noted that the polyamide composition B in each embodiment and comparative example is obtained by injection molding the corresponding polyamide composition A, the polyamide composition B in embodiments 1 to 11 is obtained by injection molding the polyamide composition A in embodiments 1 to 11, and the polyamide composition B in comparative examples 1 to 6 is obtained by injection molding the polyamide composition A in comparative examples 1 to 6, and the total amount of the polyamide composition A and the polyamide composition B is 100%.
[0080] Table 2 Weight percentage of each component of the polyamide composite material in Comparative Examples 1 to 6
[0081]
[0082] It can be seen from Table 1 and Table 2 that the polyamide composite material prepared in the present invention has good reflectivity and strength, the R460 reflectivity is not less than 80%, and the bracket tensile strength is not less than 650g.
[0083] In Comparative Example 1, no modifying agent is added. Even if phosphate and its derivatives are added, the reflectivity and strength of the obtained polyamide composite material are significantly reduced. This is because after the molecular chain is subjected to high temperature and high shear during the injection molding process, the polyamide matrix resin will break the chain, and the molecular chain will gradually become smaller, so the mechanical properties will be seriously reduced. In addition, the terminal active groups generated by the chain breaking will increase, which will also cause the material to yellow and reduce the reflectivity of the material.
[0084] When the proportion of polyamide composition B in comparative example 2 is too high, the reflectivity and strength of the obtained polyamide composite material are significantly reduced. This is because when the addition amount of polyamide composition B is too high, the rate of the fracture process is much higher than the repair speed of the modification additive, resulting in performance degradation.
[0085] When the melting point of the polyamide resin in Comparative Example 3 is too high, the reflectivity of the obtained polyamide composite material is significantly reduced.
[0086] When the thermal weight loss of the polyamide resin in Comparative Example 4 is high, the reflectivity and strength of the obtained polyamide composite material are significantly reduced.
[0087] In Comparative Example 5, if only the modifying agent is added without adding phosphate and its derivatives, the strength of the obtained polyamide composite material is significantly reduced.
[0088] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polyamide composite material, characterized in that: The invention comprises a polyamide composition A and a polyamide composition B, wherein the polyamide composition A comprises the following components in parts by weight: 35-85 parts of polyamide resin, 7-32 parts of filler, 7-32 parts of white pigment, 0.2-2 parts of modification aid, 0.2-2 parts of phosphate and its derivatives; the modification aid is a nylon chain extender; the melting point of the polyamide resin is 270-330°C, and the thermal weight loss at 370°C is less than 15%; The polyamide composition B is a polyamide composition A recycled after industrial use; The mass proportion of the polyamide composition B in the polyamide composite material is ≤85%.
2. The polyamide composite material according to claim 1, characterized in that: The polyamide composition A comprises the following components by weight: 50-70 parts of polyamide resin, 14-25 parts of filler, 14-25 parts of white pigment, 0.6-1.6 parts of modification aid, and 0.5-1 parts of phosphate and its derivatives.
3. The polyamide composite material according to claim 1, characterized in that: The mass proportion of the polyamide composition B in the polyamide composite material is 60% to 80%.
4. The polyamide composite material according to claim 1, characterized in that: The relative viscosity of the polyamide resin is 1.8 to 2.
4.
5. The polyamide composite material according to claim 1, characterized in that: The phosphates and their derivatives are one or more of potassium phosphate, sodium phosphate, potassium dihydrogen phosphate, sodium dihydrogen phosphate, phosphate ester, phosphite, and disodium dihydrogen pyrophosphate.
6. The polyamide composite material according to claim 1, characterized in that: The white pigment is at least one of titanium dioxide, zinc oxide, zinc sulfide, lead white, zinc sulfate, barium sulfate, calcium carbonate, aluminum oxide, silicon dioxide, aluminum oxide, barium carbonate, aluminum nitride, boron nitride, potassium titanate, kaolin, clay, pyrophyllite, bentonite, calcium silicate, attapulgite, aluminum borate, calcium sulfate, barium sulfate, asbestos, glass beads, silicon carbide, sericite, hydrotalcite or molybdenum disulfide; the filler is at least one of glass fiber, wollastonite, potassium titanate whisker, kaolin or mica.
7. The polyamide composite material according to claim 1, characterized in that: The nylon chain extender is at least one of anhydride chain extenders, epoxy chain extenders, oxazoline chain extenders, carbonate chain extenders, isocyanate chain extenders, polyamine chain extenders and polyol chain extenders.
8. The polyamide composite material according to claim 1, characterized in that: The polyamide composition A may further include one or more of an antioxidant, a light stabilizer, an impact modifier, a flame retardant, a fluorescent brightener, a lubricant, a plasticizer, a thickener, an antistatic agent, a release agent or a colorant.
9. A method for preparing the polyamide composite material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing and melt-extruding the components to obtain the polyamide composite material.
10. Use of the polyamide composite material according to any one of claims 1 to 8 in an LED reflective bracket.
11. An LED reflector bracket, characterized in that: It is made from the polyamide composite material described in any one of claims 1 to 8.
Citation Information
Patent Citations
Polyamide resin composite material as well as preparation method and application thereof
CN115651396A
Polyamide composite material as well as preparation method and application thereof
CN115895249A
Polyamide composite material as well as preparation method and application thereof
CN117264413A
